Enhanced Local Contractor Participation: Case of Zambia Water Supply and Sanitation Sub-Sector - Katotobwe, Chanda; Kaliba, Chabota; Kelvin Lungu Agabu (International Journal of Engineering and Management Research, 2024)
The construction sector plays a crucial role in Zambia's economic development, especially through public projects focused on areas like health, education, transport, and water and sanitation. These projects, often funded by donors, aim to improve water supply and sanitation, with key partners including Denmark, Germany, the Netherlands, Japan, Ireland, the World Bank, and the African Development Bank. While private construction projects also drive the economy, local contractor involvement in public projects is vital for Zambia's development. However, the dominance of foreign contractors in public projects is a common challenge in many developing countries, including Zambia. This research investigates the obstacles preventing local contractors from becoming main players in Zambia's construction sector, particularly in water and sanitation projects. It employs a Straussian Grounded Theory approach, proposing strategies to enhance local contractor participation. The study suggests that promoting local contractors' growth and competitiveness requires various measures, such as government confidence in their capabilities, tax incentives, procurement reforms, financial support, partnerships, segmented contracts, and fostering self-sufficiency. The research defines theoretical propositions and strategies aimed at increasing local contractor involvement in infrastructure development.